TRAINING BECOME SUCCESSFUL ENTREPRENEUR WITH SHARIA ACCOUNTING AT STAI AL FITHRAH SURABAYA - Astri Fitria, Endah Sulistyowati (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2020)
The purpose of this community of coaching service is: (1) givingstudents knowledge about entrepreneurship and motivatingstudents to carry out entrepreneurial activities,(2) givingstudents an understanding of conventional businesstransactions and business transactions that use shariacontracts, (3) giving understanding to students about simpleaccounting and sharia accounting needed in managing abusiness, and (4) improving students' skills in managing abusiness. The method is carried out through training activitieson entrepreneurship and sharia accounting for STAI Al Fitrahstudents. The result of this community service is anunderstanding of students about entrepreneurship so that theycan motivate students to become entrepreneurs and anunderstanding of students. about business transactions, simplebookkeeping and sharia accounting and improve student skillsin managing a business.